2008
DOI: 10.1007/s10350-008-9423-0
|View full text |Cite
|
Sign up to set email alerts
|

Perineal Stapled Prolapse Resection: A New Procedure for External Rectal Prolapse

Abstract: Perineal stapled prolapse resection is a new surgical procedure for external rectal prolapse, which is easy and quick to perform. Functional results and long-term recurrence rate must be investigated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 9 publications
5
66
0
2
Order By: Relevance
“…Two out of three patients (66 %) improved as regards constipation after surgery and none developed de novo constipation (Table 1). This is in accordance with the PSPR study done by Hetzer et al (Table 2), who also found no new de novo constipation in any of the patients though constipation improved in 16.6 % of patients postoperatively [1,2]. The symptom of constipation continued in one patient postoperatively with some symptomatic improvement.…”
Section: Constipationsupporting
confidence: 91%
See 4 more Smart Citations
“…Two out of three patients (66 %) improved as regards constipation after surgery and none developed de novo constipation (Table 1). This is in accordance with the PSPR study done by Hetzer et al (Table 2), who also found no new de novo constipation in any of the patients though constipation improved in 16.6 % of patients postoperatively [1,2]. The symptom of constipation continued in one patient postoperatively with some symptomatic improvement.…”
Section: Constipationsupporting
confidence: 91%
“…One patient continues to have severe incontinence that was managed conservatively with bulk forming agents. The improvement in continence after PSPR is in accordance with the PSPR study done by Hetzer et al (Table 2); in his study, severe fecal incontinence disappeared postoperatively in 90 % of patients [1,2]. Demibras et al [18] (2005) in their series of 40 cases of laparoscopic rectopexy reported improved continence in 71 % of patients.…”
Section: Incontinencesupporting
confidence: 86%
See 3 more Smart Citations